Pelayanan Administrasi Kependudukan melalui Program 'Desaku Tuntas' - Sadidah, Laily Rahmah; Ulum, Mochamad Chazienul (Jurnal Ilmiah Publika, 2025)
The vast territory of Malang Regency has prompted the Population and Civil Registration Office of Malang Regency to bring services closer to the community. The 'Desaku Tuntas' program is a population administration service program implemented at the village/sub-district level. This study aims to analyze the implementation of the 'Desaku Tuntas' program in population administration services in Malang Regency using David C. Korten's program implementation theory. This research employs a qualitative research method with a case study variant. The findings show that the program is in accordance with community needs, the implementing organization has adequate competence, and the compatibility between the implementing organization and the beneficiaries is good. However, there is not yet a specific policy or budget allocation for this program.